2005
DOI: 10.1038/sj.onc.1208819
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of EB1 in human esophageal squamous cell carcinoma (ESCC) may promote cellular growth by activating β-catenin/TCF pathway

Abstract: Esophageal squamous cell carcinoma (ESCC) has a multifactorial etiology involving environmental and/or genetic factors. End-binding protein 1 (EB1), which was cloned as an interacting partner of the adenomatous polyposis coli (APC) tumor suppressor protein, was previously found overexpressed in ESCC. However, the precise role of EB1 in the development of this malignancy has not yet been elucidated. In this study, we analysed freshly resected ESCC specimens and demonstrated that EB1 was overexpressed in approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 20 publications
2
73
1
Order By: Relevance
“…The Wnt/b-catenin signaling pathway is essential for embryonic development and aberrant activation has been associated with the progression of many cancer types, including ESCC (5,6). Pairedlike homeodomain transcription factor 2 (PITX2) is a member of the bicoid-related homeodomain family and a downstream effecter of Wnt signaling, which activates the expression of target genes required for cell proliferation and survival (7).…”
Section: Introductionmentioning
confidence: 99%
“…The Wnt/b-catenin signaling pathway is essential for embryonic development and aberrant activation has been associated with the progression of many cancer types, including ESCC (5,6). Pairedlike homeodomain transcription factor 2 (PITX2) is a member of the bicoid-related homeodomain family and a downstream effecter of Wnt signaling, which activates the expression of target genes required for cell proliferation and survival (7).…”
Section: Introductionmentioning
confidence: 99%
“…For example, end-binding protein 1 (EB1) over-expression may contribute to the development of ESCC by activating the ß-catenin/TCF pathway (2). Another report demonstrated that the Notch1 signaling pathway is activated in ESCC, and that it can inhibit cell proliferation and induce apoptosis in human ESCC cells (3).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this interaction in carcinogenesis is shown by the finding that mutation of the APC tumor suppressor that disrupts its interaction with EB1 occurs commonly in the familial and sporadic colon cancers (Su et al, 1995). A recent finding has indicated that EB1 is overexpressed in many human esophageal squamous cell carcinoma (ESCC), and may play a role in the development of ESCC by affecting APC function and activating the b-catenin/TCF pathway (Wang et al, 2005). Recently, an APC homolog APC2 has been identified and shown to be predominantly expressed in the central nervous system (Nakagawa et al, 1998;van Es et al, 1999).…”
Section: Introductionmentioning
confidence: 99%